Isolasi dan Karakteristik Bakteri Pendegradasi Selulosa pada Ampas Tebu Kuning (Bagasse) - Irwan Lovadi, Krispina Nofu, Siti Khotimah, (Jurnal Protobiont, 2014)
Cellulose is the main carbohydrate synthesized by plants and it occupies almost 60% of the components of the structure of plants. Natural process of decomposition of cellulose requires the help of microorganisms that secrete the enzyme cellulase. Bagasse contains 32-34% cellulose. This study aims to determine the cellulose degrading bacteria of yellow bagasse and know the ability of the bacteria to degrade cellulose bagasse. The samples were taken from ice-cane seller in the District of South Pontianak. To isolate of cellulose degrading bacteria, the dilution method of Carboxymethylcellulose (CMC) was used and HC test was performed on solid CMC. Dry weight of test was performed using a fresh bagasse as a source of cellulose. The results showed that there are fifteen pure isolates of cellulose degrading bacteria consisting of eight genera, namely Psedomomas, Bacillus, Nocardia, Kurthia, Vibrio, Flavobacterium, Neissera, and Micrococcus. AT3BPS2 isolates (Nocardia) has the largest ratio of 2.67 HC. Isolates that have the lowest HC constellation is AT1BPS1 isolates (Pseudomonas) 1.06. Isolates that has the highest cellulose degradation ability is AT1BPS2 (Pseudomonas) at 19.28% and isolates with the lowest degradation ability is AT3BPS2 (Nocardia) at 7.21%.